SysML for systems engineering : a model based approach - Holt, Jon (Institution of Engineering and Technology, 2013)
The book has 16 chapters dealing with the following subjects: model-based systems engineering; MBSE concepts; SysML notation; systems modelling; diagramming guidelines; expanded process modelling; expanded requirements modelling; and architectural frameworks.
Keywords: SysML (Computer science); Systems engineering.; elektronické knihy; electronic books